Apparent Stability and Subtle Change in Surface and Subsurface Soil Carbon and Nitrogen under a Long‐Term Fertilizer Gradient. Issue 2 (20th April 2017) - Collier, Sarah M.; Ruark, Matthew D.; Naber, Mack R.; Andraski, Todd W.; Casler, Michael D.
Abstract : Core Ideas: Long‐term fertilizer rate affected soil properties to 1 m under continuous corn. Inorganic N fertilization was a benefit rather than a detriment to soil C and N. The most productive treatments maintained but did not build soil C and N. All fertilizer rate treatments had less topsoil than the field edge. Uncertainty exists regarding the depth and extent to which agricultural practices affect soil properties, in particular soil organic C (SOC). In this study we examined the impact of 53 yr of continuous corn ( Zea mays L.) receiving varying rates of inorganic N fertilizer with complete stover return on soil properties including SOC, total N, and bulk density (BD) to a depth of 1 m. In the treatment receiving virtually no applied N there was a significant reduction in soil N content at 0 to 30 cm over the study period, while the treatment receiving N in excess of recommended application levels was similar to the treatment receiving recommended rates of N fertilizer. Trends in SOC content were similar to those for total N, but a significant treatment effect was detectable throughout the entire 1‐m soil profile sampled. Over the course of the study, all experimental fields appeared to have lost approximately 6 cm of topsoil through erosion, with the lowest N rate plots subsiding a further 2 cm due to compaction. Despite using disruptive management practices (moldboard plowing and application of anhydrous ammonia), declines in soil C and N content were not apparent for this soil type under conditions of low slope and the linear gains in productivity realized under the two higher N rate treatments. Thus N fertilizer was a benefit to this cropping system, rather than a detriment, and was sufficient to allow maintenance—but not building—of SOC.